2020
DOI: 10.1021/acsanm.0c00797
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Polymerase Chain Reaction Using Electroactive Graphene Oxide Nanoparticles as Detection Labels

Abstract: Electroactive nanocarbon tags are used in this work to label the DNA primers for the polymerase chain reaction (PCR) amplification of Cauliflower Mosaic Virus 35S promoter sequence, one of the most common markers for the detection of genetically modified organisms (GMOs). The PCR product carrying the electrochemical label can be directly detected on miniaturized electrodes, with the working signal being correlated to the reduction of oxygen-containing groups on the nanocarbon surface. A linear relationship was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Adapted with permission from Ref. [ 54 ]; (C) Electrochemical PCR scheme using graphene oxide nanoparticles as labels for DNA primers: (i) Electrochemical detection on miniaturized electrode; (ii) nanographene oxide reduction current vs PCR cycle number for positive (red) and negative control (blue) [ 26 ]. Reproduced with permission from Ref.…”
Section: Electrochemistry For the Detection Of Coronavirus-induced Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Adapted with permission from Ref. [ 54 ]; (C) Electrochemical PCR scheme using graphene oxide nanoparticles as labels for DNA primers: (i) Electrochemical detection on miniaturized electrode; (ii) nanographene oxide reduction current vs PCR cycle number for positive (red) and negative control (blue) [ 26 ]. Reproduced with permission from Ref.…”
Section: Electrochemistry For the Detection Of Coronavirus-induced Inmentioning
confidence: 99%
“…Our group has recently made use of electrochemical PCR to successfully detect genetically modified organisms by amplifying the Cauliflower Mosaic Virus 35S promoter sequence with the help of electroactive nanographene oxide nanoparticles as labels for the DNA primers used in PCR amplification step [ 26 ]. Electrochemical PCR has been already employed for the detection of Influenza A (AH1pdm) virus [ 58 ] using methylene blue as electroactive intercalator, which electrochemical signal is inversely correlated to the amount of PCR product [ 58 ].…”
Section: Electrochemistry For the Detection Of Coronavirus-induced Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical biosensors are one of the earliest and most mature DNA detection technologies with unique advantages. , Because signals can be measured directly without requiring an expensive, complicated, and fault-prone transduction device, electrochemical biosensors are of simple operation, high sensitivity, low cost, and easy portability, providing a promising approach for the field detection of GMOs. However, sensitivity and specificity need to be further improved because the analyte concentration is usually very low without PCR amplification. Obviously, to construct an electrochemical biosensor for GMOs with high sensitivity and specificity, a novel signal amplification strategy and a new recognition system are greatly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of works are shown in the literature whereby DNA oligonucleotides, proteins, antibodies and enzymes used as bio‐recognition elements are immobilized onto the graphene surface not only by physical adsorption, but also through covalent conjugation with the OCGs . Furthermore, it has been shown that OCGs can play a role in the generation of the working signal by exploiting their intrinsic optical and electrochemical properties . However, on the other hand, the electrical conductivity of graphene is largely impaired when significant amounts of OCGs are introduced, and this will have detrimental effects on the use of the graphene material especially for electrochemical applications including biosensing.…”
Section: Introductionmentioning
confidence: 99%